2007
DOI: 10.1504/ijwoe.2007.013615
|View full text |Cite
|
Sign up to set email alerts
|

Understanding emotional responses to anticipated change: the case of introducing electronic care plans in hospitals

Abstract: This study aimed to address the range and complexity of emotions involved in the anticipation of change at work through adopting a contextual approach to understanding emotions and change. A qualitative study was conducted to explore nurses` emotional responses towards the anticipated introduction of electronic care plans. Emotional responses revolved around three issues in particular: Envisioning the change process, meeting professional standards in the future, and everyday work situation following anticipate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Most importantly, insight into emotional experiences and their perceived causes provides a more specific picture of individuals’ concerns and what they consider to be important, following the fact that emotions communicate what values, needs, and goals are at stake in a particular situation, and are adaptive because they ready individuals for action (Landman, 1996, Lazarus, 1991). Previous research has demonstrated that negative emotional states in a change context emerge as a consequence of not being able to do one’s job properly, and the extra hassle involved in maintaining already established standards for work following organizational change (Giæver, 2007; Kiefer, 2005; 2002). Hence, exploring employees’ negative emotional experiences, along with their perceived causes, may provide a better point of departure for understanding the ways in which a change situation is problematic and should be attended to.…”
Section: Why Examine Negative Emotional Experiences? a Contextual Per...mentioning
confidence: 99%
“…Most importantly, insight into emotional experiences and their perceived causes provides a more specific picture of individuals’ concerns and what they consider to be important, following the fact that emotions communicate what values, needs, and goals are at stake in a particular situation, and are adaptive because they ready individuals for action (Landman, 1996, Lazarus, 1991). Previous research has demonstrated that negative emotional states in a change context emerge as a consequence of not being able to do one’s job properly, and the extra hassle involved in maintaining already established standards for work following organizational change (Giæver, 2007; Kiefer, 2005; 2002). Hence, exploring employees’ negative emotional experiences, along with their perceived causes, may provide a better point of departure for understanding the ways in which a change situation is problematic and should be attended to.…”
Section: Why Examine Negative Emotional Experiences? a Contextual Per...mentioning
confidence: 99%